7z-6=3z+4

Simple and best practice solution for 7z-6=3z+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7z-6=3z+4 equation:


Simplifying
7z + -6 = 3z + 4

Reorder the terms:
-6 + 7z = 3z + 4

Reorder the terms:
-6 + 7z = 4 + 3z

Solving
-6 + 7z = 4 + 3z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-3z' to each side of the equation.
-6 + 7z + -3z = 4 + 3z + -3z

Combine like terms: 7z + -3z = 4z
-6 + 4z = 4 + 3z + -3z

Combine like terms: 3z + -3z = 0
-6 + 4z = 4 + 0
-6 + 4z = 4

Add '6' to each side of the equation.
-6 + 6 + 4z = 4 + 6

Combine like terms: -6 + 6 = 0
0 + 4z = 4 + 6
4z = 4 + 6

Combine like terms: 4 + 6 = 10
4z = 10

Divide each side by '4'.
z = 2.5

Simplifying
z = 2.5

See similar equations:

| -8k+4=-6k+20 | | 9j-4=5j+28 | | -6u+7=u+70 | | y/5=-20 | | 11u+1=6u-29 | | -x-4=-4x+2 | | -8g+7=-g+63 | | 70=6x-14 | | 7j-4=3j-28 | | 10e-4=4e-10 | | 2a+4=-3a-36 | | -2q+6=3q-24 | | 2x-1=-x-28 | | 6h-4=h-9 | | 9y-1=5y+15 | | 12+8=5d+57 | | 7(3g+8)/4=35 | | 8-32x+27x-3=0 | | 4(x-5)=-1.6 | | 12d+8=8d+16 | | 13=5c-9 | | 9e-7=28.1 | | 8(x-2)=26.4 | | 2(3y-6)=-18 | | 2(7v-4)=-22 | | 3(4k-4)=60 | | 4(6u-4)=152 | | 3(5t+2)=-84 | | 5(4q+3)=-145 | | 8e-7=17 | | 16.2=2c-2 | | 5(4x-4)=-40 |

Equations solver categories